A Chinese route to sustainability: Postsocialist transitions and the construction of ecological civilization. (17th May 2018) - Liu, Chen; Chen, Lily; Vanderbeck, Robert M.; Valentine, Gill; Zhang, Mei; Diprose, Kristina; McQuaid, Katie
Abstract: This article explores the concept of sustainability in a postsocialist context through an analysis of official discourses relating to sustainability in more than 700 articles published in the Chinese‐language newspaper People's Daily in 2015. The Chinese conception of sustainability, which emerges as a top‐down model built upon traditional ideologies and Chinese socialist legacies, inclusive of economic growth, environmental sustainability, social justice and quality of life. This Chinese official discourse of sustainability places less emphasis on individuals' rights and more on the state's interests, and is encompassed in the Chinese concept of the "ecological civilization." This article argues that if we are to build a full picture of the internationalized idea of sustainability we need to adopt a more international approach to thinking about the issue, drawing upon the sustainability‐related discourses constructed from different national contexts using local languages and rhetoric.